MANAJEMEN SARANA DAN PRASARANA DALAM PROSES PEMBELAJARAN DI PAUD AGUSTINUS NATANANGGE - Surisna So'o, Sonyalia; Nama Koten, Angelikus; Paulin Nalle, Andriani; Margiani, Kristin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Management of educational facilities and infrastructure is an essential aspect of improving the quality of the learning process in Early Childhood Education (ECE). This study aims to describe the management of educational facilities and infrastructure in supporting the learning process at PAUD Agustinus Natanangge. This research employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation and analyzed using the Miles and Huberman interactive model. The findings indicate that the management of educational facilities and infrastructure has been implemented through planning, procurement, inventory, utilization, maintenance, and disposal. These management practices have supported the learning process; however, limited financial resources remain the main challenge in fulfilling the school's facility needs. Therefore, support from the government and other stakeholders is required to improve the management of educational facilities and infrastructure and enhance the quality of learning.